If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(-8 + -2x) = 110 (-8 * -5 + -2x * -5) = 110 (40 + 10x) = 110 Solving 40 + 10x = 110 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-40' to each side of the equation. 40 + -40 + 10x = 110 + -40 Combine like terms: 40 + -40 = 0 0 + 10x = 110 + -40 10x = 110 + -40 Combine like terms: 110 + -40 = 70 10x = 70 Divide each side by '10'. x = 7 Simplifying x = 7
| 2(3x-2)=7x-10 | | 3(5n-5)+8=-97 | | 5(x+2)+4=19 | | 3(x-2)=7-2(5-x) | | 4+4w=-16 | | -7(m-8)=91 | | 6(2*-8)+3=15 | | 4w+15=91 | | 4(y+2)=5 | | -30=-2v | | 11x-45=-12 | | 8(x-1)+2(x-1)=90 | | -50+x+x+x=-11 | | ab=3x+12 | | 4c-5c+8.4=3.6-2c-4.2 | | 63=3v | | 87+x=120 | | -45+x=-31 | | 4+6x=7+2x | | -2(-3x+2)=-6 | | 3(2b-4)=5(b+2) | | 105x^2-182x+56=0 | | 7a+8=8a-2 | | 3(4x+7)+9(x-1)=180 | | 3x-5-4x=6-2x | | s+1.2=-.2 | | 107-2x=25x+23 | | 3x-2=3(x-0.6666666666666666) | | x^4+12x^2-27=0 | | 63y-42=64y | | 7x-1+22(x-1)=180 | | 6(x-4)+9=2x+4(-3+x) |